2012
DOI: 10.1590/s0102-695x2012005000075
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in the pigment composition of natural population of Gracilaria domingensis (Gracilariales, Rhodophyta)

Abstract: Abstract:The concentrations of phycobiliproteins (phycoerythrin and phycocyanin), chlorophyll-a and total soluble proteins were determined monthly in three strains (red, green and brown) of Gracilaria domingensis (Kützing) Sonder ex Dickie, collected from natural populations on the coast of Rio Grande do Norte, Brazil. In all the strains, pigment and protein concentrations were higher in the months of less sunlight and greater nitrogen availability and decreased gradually with increased sunlight and decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 36 publications
(32 reference statements)
4
13
0
3
Order By: Relevance
“…Higher concentrations of the photosynthetic pigments chlorophyll a and phycobiliproteins were registered in algae grown at 20 cm. This result is in agreement with previous studies (Eswaran et al 2002;MarinhoSoriano 2012;Pereira et al 2012), which also observed an increase in the pigment concentration associated with a decrease in irradiance. This increment in pigment concentration is related to an increase in the size of the light-harvesting complex and the number of photosystems, resulting in an amplified ability to collect incident light and convert it into energy.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Higher concentrations of the photosynthetic pigments chlorophyll a and phycobiliproteins were registered in algae grown at 20 cm. This result is in agreement with previous studies (Eswaran et al 2002;MarinhoSoriano 2012;Pereira et al 2012), which also observed an increase in the pigment concentration associated with a decrease in irradiance. This increment in pigment concentration is related to an increase in the size of the light-harvesting complex and the number of photosystems, resulting in an amplified ability to collect incident light and convert it into energy.…”
Section: Discussionsupporting
confidence: 94%
“…These two components play an important role in nitrogen storage, and are the primary pools of metabolized nitrogen when environmental nitrogen concentrations are reduced. Moreover, the fact that the red strain synthesizes more phycoerythrin makes it more competitive in capturing solar energy and performing photosynthesis (Pereira et al 2012). This ability contributes to higher growth and thus better environmental performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phycoerythrin content in Gloiopeltis furcate (Postels et Ruprecht) J. Agardh, and Porphyra yezoensis Ueda correlated significantly with nitrogen content (Mizuta et al 2002). Pereira et al (2012) found that nitrate was assimilated as PC and PE by Porphyra dioica Brodie and Irvine and phycoerythrin PE was the main form of nitrogen pool, while, phosphorus participates in the formation of biomolecules such as nucleic acids, proteins and phospholipids. In the same year, Marinho-Soriano (2012) showed the importance of NO 3 for the biosynthesis of this pigment, demonstrated the positive correlation between them.…”
Section: Discussionmentioning
confidence: 96%
“…Both PE and PC concentrations showed clear trends of decreasing concentration with increasing temperature (Latham 2008). Pereira et al (2012) stated that the concentration of R-Phycoerythrin (RPE) and Chl-a in Gracilaria bursapastor is showed maximum values in the winter and minimum values in summer.…”
Section: Discussionmentioning
confidence: 98%